Chicken γδ T cells proliferate upon IL-2 and IL-12 treatment and show a restricted receptor repertoire in cell culture - Linti, Antonia E.; Göbel, Thomas W.; Früh, Simon P. (Frontiers in Immunology, 2024)
In chickens, γδ T cells represent a large fraction of peripheral T cells; however, their function remains largely unknown. Here, we describe the selective in vitro expansion of γδ T cells from total splenocytes by stimulation with the cytokines IL-2 and IL-12. Under these conditions, γδ T cells proliferated preferentially and reached frequencies of >95% within three weeks. Although IL-2 alone also triggered proliferation, an increased proliferation rate was observed in combination with IL-12. Most of the expanded cells were γδ TCR and CD8 double-positive. Splenocytes sorted into TCR1+CD8+, TCR1highCD8−, and TCR1lowCD8− subsets proliferated well upon dual stimulation with IL-2/IL-12, indicating that none of the three γδ T cell subsets require bystander activation for proliferation. TCR1+CD8+ cells maintained CD8 surface expression during stimulation, whereas CD8− subpopulations showed varied levels of CD8 upregulation, with the highest upregulation observed in the TCR1high subset. Changes in the γδ T-cell receptor repertoire during cell culture from day 0 to day 21 were analyzed by next-generation sequencing of the γδ variable regions. Overall, long-term culture led to a restricted γ and δ chain repertoire, characterized by a reduced number of unique variable region clonotypes, and specific V genes were enriched at day 21. On day 0, the δ chain repertoire was highly diverse, and the predominant clonotypes differed between animals, while the most frequent γ-chain clonotypes were shared between animals. However, on day 21, the most frequent clonotypes in both the γ and δ chain repertoires were different between animals, indicating that selective expansion of dominant clonotypes during stimulation seems to be an individual outcome. In conclusion, IL-2 and IL-12 were sufficient to stimulate the in vitro outgrowth of γδ T cells. Analyses of the TCR repertoire indicate that the culture leads to an expansion of individual T cell clones, which may reflect previous in vivo activation. This system will be instrumental in studying γδ T cell function.